(untitled) (Nexo Revista Científica, 2022)
Centralized water supply in remote settlements is often difficult or impossible, so there is a need to use a non-centralized water supply. The article develops a method for an expert assessment of the negative change in the state of underground karst waters based on a paired analysis of complex indicators of the protection of the aquifer. To assess the vulnerability of non-centralized water supply sources, five factors are used, including the geological structure of the territory, the level of surface and underground runoff, the development of the karst network, precipitation regime electrical conductivity, and mineralization of groundwater. The test was performed using the method of inversely weighted distances (IDW). The vulnerability assessment of karst waters was carried out in the area of 10 key control points identified during the deployment of the hydrogeological control system in 2017. Based on various geological and hydrological indicators, the discrepancy between the vulnerability assessment of karst waters was no more than 15 %. The conditions under which it is advisable to use direct measurements or geoelectric methods to monitor karst groundwater’s state are identified.